2021
DOI: 10.1177/21582440211011463
|View full text |Cite
|
Sign up to set email alerts
|

Transition From Subsistence Agriculture to Rubber Plantations in Northern Laos: Analysis of Household Livelihood Strategies by Ethnicity and Gender

Abstract: The study examined livelihood changes in eight villages in Luang Namtha province of northern Lao PDR following the expansion in rubber plantations and analyzed its impact on gender roles and relations. All study villages are engaged in rubber production, but the impact is shaped by the context and history of the particular location. The study has demonstrated the importance of feminist political ecologist approach in analyzing the conjuncture and intersectionality, as well as the location that shapes these con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This type of landscape structure had different agricultural and deforestation histories, and is mostly dedicated to rubber and eucalyptus plantations that have increased exponentially in the country. Part of the present study was undertaken on a large rubber plantation in northern Laos (site 4), which covered 33,000 ha in 2016 and was occupied by various ethnic groups (Kusakabe & Chanthoumphone, 2021 ); more rubber plantation areas now extend to the center and to the south. Most of the deforestation happened several years before sampling, resulting in a single unfragmented rubber plantation.…”
Section: Methodsmentioning
confidence: 99%
“…This type of landscape structure had different agricultural and deforestation histories, and is mostly dedicated to rubber and eucalyptus plantations that have increased exponentially in the country. Part of the present study was undertaken on a large rubber plantation in northern Laos (site 4), which covered 33,000 ha in 2016 and was occupied by various ethnic groups (Kusakabe & Chanthoumphone, 2021 ); more rubber plantation areas now extend to the center and to the south. Most of the deforestation happened several years before sampling, resulting in a single unfragmented rubber plantation.…”
Section: Methodsmentioning
confidence: 99%
“…Better information and understanding with respect to policy, tax, and the legal system would reduce negative impacts on business growth and livelihoods [81]. Agripreneurs reported that "unofficial" payments persist, adding to calls in the literature for transparency in the system [53,69,82].…”
Section: Perceived Limitations To Agripreneurhsipmentioning
confidence: 99%
“…the intercropping practices of the young rubber with annual crops such as legumes, corn, sesame rice, cassava, papaya, and bananas, are a factor increasing annual croplands in the classified maps. These issues are also found in other rubber-growing areas (Stroesser et al 2018;Kusakabe and Chanthoumphone 2021;Huang et al 2022;Su et al 2022). In summary, the transition between annual and perennial croplands is due to the effects of agricultural development policies and practices, natural conditions, and product price fluctuations in the market.…”
Section: Factors Affecting Land-use Change From 1995 To 2020mentioning
confidence: 67%